2005
DOI: 10.1158/0008-5472.can-04-4126
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for Focal Adhesion Kinase in the Early Phase of Mammary Adenocarcinoma Lung Metastasis Formation

Abstract: An increased expression of focal adhesion kinase (FAK) in a variety of cancers is associated with a poor disease prognosis. To study the role of FAK in breast tumor growth and metastasis formation, we used conditional doxycycline-regulated expression of a dominant-negative acting splice variant of FAK, FAK-related non-kinase (FRNK), in MTLn3 mammary adenocarcinoma cells in a syngeneic Fischer 344 rat tumor and metastasis model. In cell culture, doxycycline-mediated expression of FRNK inhibited MTLn3 cell sprea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
101
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(106 citation statements)
references
References 30 publications
4
101
1
Order By: Relevance
“…Several studies have indicated that FAK may have a direct role in tumour growth and cell survival (Xu et al, 1996(Xu et al, , 1998Sonoda et al, 1999Sonoda et al, , 2000Aguirre Ghiso, 2002;Hecker et al, 2002Hecker et al, , 2004van Nimwegen et al, 2005). However, there are also published data showing that FRNK expression induces defects on migration and/or invasion without effects on cell survival or proliferation (Han et al, 2004;.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have indicated that FAK may have a direct role in tumour growth and cell survival (Xu et al, 1996(Xu et al, , 1998Sonoda et al, 1999Sonoda et al, , 2000Aguirre Ghiso, 2002;Hecker et al, 2002Hecker et al, , 2004van Nimwegen et al, 2005). However, there are also published data showing that FRNK expression induces defects on migration and/or invasion without effects on cell survival or proliferation (Han et al, 2004;.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are also published data showing that FRNK expression induces defects on migration and/or invasion without effects on cell survival or proliferation (Han et al, 2004;. Indeed, impairment of cell proliferation and survival after FRNK expression in carcinoma cells has been associated with high levels of overexpression Golubovskaya et al, 2002;van Nimwegen et al, 2005). Therefore, the contradictory effects on cell growth or survival may be due to the levels of functional FAK in the presence of FRNK or FAK siRNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In experimental metastasis assays after tail vein injection, FRNK expression in v-Src-transformed fibroblasts (Hauck et al, 2002b), B16-F10 (AbdelGhany et al, 2002) and MTLn3 breast carcinoma cells (van Nimwegen et al, 2005) blocked tumor cell colonization of lungs. In various tumor cells, exogenous FRNK expression is correlated with reduced levels of protease secretion (Hauck et al, 2002b;Hess et al, 2005) or slower growth (van Nimwegen et al, 2005). Although FRNK acts to inhibit FAK activity, it also encompasses multiple protein binding sites and may act to sequester signaling proteins away from FAK.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas high levels of FRNK can promote cell apoptosis (Xu et al, 2000;Golubovskaya et al, 2002), FRNK expression can also reduce tumor growth by promoting tumor dormancy and by inhibiting cell proliferation (Aguirre Ghiso, 2002;van Nimwegen et al, 2005). Low levels of FRNK expression have revealed the importance of FAK activity in promoting tumor cell migration (Slack et al, 2001) and in generating an invasive cell phenotype (Hauck et al, 2001(Hauck et al, , 2002bHsia et al, 2003;.…”
Section: Introductionmentioning
confidence: 99%